Quality Management of Prehospital Pediatric Respiratory Distress and Airway Programs: An NAEMSP Position Statement and Resource Document. (4th January 2022) - Mandt, Maria; Harris, Matthew; Lyng, John; Moore, Brian; Gross, Toni; Gausche-Hill, Marianne; Donofrio-Odmann, J. Joelle
Abstract: The unique challenges of pediatric respiratory and airway emergencies require the development and maintenance of a prehospital quality management program that includes pediatric-focused medical oversight and clinical care expertise, data collection, operational considerations, focused education, and clinician competency evaluation. NAEMSP recommends: Medical director oversight must include a focus on pediatric airway and respiratory management and integrate pediatric-specific elements in guideline development, competency assessment, and skills maintenance efforts. EMS agencies are encouraged to collaborate with medical professionals who have expertise in pediatric emergency care to provide support for quality management initiatives in pediatric respiratory distress and airway management. EMS agencies should define quality indicators for pediatric-specific elements in respiratory distress and airway management and benchmark performance based on regional and national standards. EMS agencies should implement both quantitative (objective) and qualitative (subjective) measures of performance to assess competency in pediatric respiratory distress and airway management. EMS agencies choosing to incorporate pediatric endotracheal intubation or supraglottic airway insertion must use pediatric-specific quality management benchmarks and perform focused review of advanced airway management.